2015
DOI: 10.1371/journal.pone.0133879
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin Concentrations Do Not Predict Sustained Virological Response in HIV/HCV-Coinfected Patients Treated with Ribavirin and Pegylated Interferon in the Swiss HIV Cohort Study

Abstract: BackgroundRibavirin (RBV) is an essential component of most current hepatitis C (HCV) treatment regimens and still standard of care in the combination with pegylated interferon (pegIFN) to treat chronic HCV in resource limited settings. Study results in HIV/HCV-coinfected patients are contradicting as to whether RBV concentration correlates with sustained virological response (SVR).MethodsWe included 262 HCV treatment naïve HIV/HCV-coinfected Swiss HIV Cohort Study (SHCS) participants treated with RBV and pegI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…We showed that at week 8 of treatment, ribavirin reached steady‐state, which fits the long elimination half‐life of 300 h . The steady‐state ribavirin plasma concentrations found in this study were in the same range as previously published in HIV/HCV co‐infected patients . However, these plasma concentrations remained lower than reported ribavirin plasma concentrations in mono‐infected patients .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We showed that at week 8 of treatment, ribavirin reached steady‐state, which fits the long elimination half‐life of 300 h . The steady‐state ribavirin plasma concentrations found in this study were in the same range as previously published in HIV/HCV co‐infected patients . However, these plasma concentrations remained lower than reported ribavirin plasma concentrations in mono‐infected patients .…”
Section: Discussionsupporting
confidence: 85%
“…This could be driven by the increasing number of patients of which ribavirin plasma concentrations were available towards weekend 48. The relation between ribavirin plasma concentrations and SVR remains controversial, as both negative and positive results have been published about this topic . These inconsistent results might be caused by, for example, differences in treatment, heterogeneity of populations, variation in analytical assays and small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-individual differences in RBV disposition are well documented and common side-effects, such as anaemia, have been associated with high RBV exposure [3]. Studies have suggested that positive treatment outcomes and adverse events may be associated with RBV concentration thresholds [4] but contradictory data exist [5], perhaps consistent with its multiple mechanisms of action [6,7]. The instability of drug concentrations in collected samples [8] further complicates RBV therapeutic monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the association between RBV steady‐state plasma level and sustained virological response (SVR) in HCV mono‐ and HIV/HCV co‐infected patients show contradictory results, possibly due to their small sample sizes and retrospective nature . Moreover, studies on RBV steady‐state plasma levels in DAA‐treated patients are scarce.…”
Section: Introductionmentioning
confidence: 99%